Single-site ventricular pacing via the coronary sinus in patients with tricuspid valve disease. Issue 4 (1st March 2017) - Noheria, Amit; van Zyl, Martin; Scott, Luis R; Srivathsan, Komandoor; Madhavan, Malini; Asirvatham, Samuel J; McLeod, Christopher J
Abstract: Aims: To evaluate coronary sinus single-site (CSSS ) left ventricular pacing in adult patients with normal left ventricular ejection fraction (LVEF) when traditional right ventricular lead implantation is not feasible or is contraindicated. Methods and results: We performed a retrospective analysis of 23 patients with tricuspid valve surgery/disease who received a CSSS ventricular pacing lead to avoid crossing the tricuspid valve. Two matched control populations were obtained from patients receiving (i) conventional right ventricular single-site (RVSS ) leads and (ii) coronary sinus leads for cardiac resynchronization therapy (CSCRT ). Main outcomes of interest were lead stability, electrical lead parameters and change in LVEF during long-term follow-up. Successful CSSS pacing was accomplished in all 23 patients without any procedural complications. During the 5.3 ± 2.8-year follow-up 22/23 (95.7%) leads were functional with stable pacing and sensing parameters, and 1/23 (4.3%) was extracted for unrelated reasons. Compared to CSSS leads, the lead revision/abandonment was similar with RVSS leads (Hazard ratio (HR) 0.87, 95% confidence interval (CI) 0.03, 22.0), but was higher with CSCRT leads (HR 7.41, 95% CI 1.30, 139.0). There was no difference in change in LVEF between CSSS and RVSS groups (–2.4 ± 11.0 vs. 1.5 ± 12.8, P =  0.76), but LVEF improved in CSCRT group (11.2 ± 16.5%, P =  0.002). Fluoroscopy times were longer during implantation of CSSS compared to RVSS leads (25.6 ± 24.6 min vs. 12.3 ± 18.6 min, P =  0.049). Conclusion: In patients with normal LVEF, single-site ventricular pacing via the coronary sinus is a feasible, safe and reliable alternative to right ventricular pacing.